Active tourism vs. ‘Krajoznawstwo’: considerations about Polish history and geography in the context of sightseeing the area around the Lake Malta in Poznan - Rozmiarek, Mateusz; Poczta, Joanna (Journal of Education, Health and Sport, 2021)
Among the fastest growing branches of the world economy, tourism is considered to be one of the main ones. It provides an opportunity to travel and explore the surrounding reality, including the diverse landscape. One of the most popular forms of tourism is still active tourism, which has a mass range and thus offers a more accessible educational offer in the field of natural and cultural heritage, history or geography. In Poland this is referred as ‘Krajoznawstwo’. The concept has not yet found an equivalent name in English, but it is very much related to tourism. In the Polish capital of Greater Poland region – Poznan, the area around Lake Malta is one of the areas where one can see many objects of interest for people who collect information about the area in the context of gathering knowledge about the country and the region. Not only a geographer or a biologist, but also all those who are comprehensively interested in the natural and cultural heritage, and in the future even in the history of the local participants in the Olympic Games, will find some information there. The main goal of the study is to is to show that “krajoznawstwo” has many features in common with active tourism and can thus be translated into English, where there is no clear equivalent word. The second goal is to present the area of the Malta Lake in Poznań as a case study, a place for the realization of sightseeing interests and active tourism.